Creating Value for Dental Visits in Public Health - Dr Sandeep Chopra; Dr Ramini Shankumar; Dr Parul Marwaha; Ms Kelsey Ingram; Prof Rodrigo Mariño (International Dental Journal, 2023)
Aim or Purpose: The “Value for Visits” approach, adapted from the Value Based Oral Health Care (VBOHC) Model was introduced by Monash Health Dental Services in 2020. The VBOHC model provides better oral health outcomes for MHDS‘ clients. The aim of this study was to assess the VBOHC model by reviewing and comparing courses of care outcomes before and after the model's implementation. Materials and Methods: All general courses of care (CoC) in 2019 and 2022 were audited, and a review of courses of care was conducted. The 2019 CoCs included solely patients whose treatment had begun prior to COVID-19 restrictions being imposed.Analysis involved investigating 10 CoCs for each clinician working at an MDHS dental clinic. The review did not include new staff (less than 3 months) or staff primarily working in the School Dental program. A thorough auditing was conducted into the ways in which general oral health care was provided to public patients. Results: In 2019 the total number of clients seen was 4240 with an average patient receiving 4.05 appointments over 6.37 months, and seeing 2.61 clinicians. In 2022, under the VBOHC model, the total number of clients seen was 5644. The average number of appointments to complete a CoC was 2.70 over 5.39 months. The number of clinicians seen was 1.10. Conclusions: Data showed that after implementation of the VBOHC model there was improvement in the efficiency of oral health care provision. Full implementation of the model would provide superior continuity of care, and overall better oral health outcomes for public dental patients.